Draft Seventh Five Year Plan (1985-90) and Annual Plan 1985-86 Vol. II Government of Uttar Pradesh - Planning Commission (Planning Commission, 1985)
Modernisation of Upper Ganga Canal system (World Bank Project) —The project envisaged the construction of a lined parallel Upper Ganga canal new scapes and additional new channels for areas not served by outlets of existing Upper Ganga Canal its gross command in addition to re-modelling of existing Upper Ganga canal system particularly Hydraulic structure.
Government of Uttar Pradesh, Planning Department